2014
DOI: 10.1021/sc400545d
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Precipitation of Softwood Kraft Lignin: Isolation of Narrow Fractions Common to a Variety of Lignins

Abstract: In a manner similar to crude oil, technical lignins need refining if their potential as reactive polyphenols of well-defined molecular weight polymers and oligomers is to be actualized. In this paper, we demonstrate that a continuum of narrow fractions can be isolated by the incremental addition of a nonpolar solvent (hexanes) in a polar (acetone) solution of softwood wood kraft lignin. Three distinct commercial samples of softwood kraft lignin were used to examine the validity of the developed protocol using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
189
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(214 citation statements)
references
References 33 publications
23
189
0
2
Order By: Relevance
“…Thus, ultrafiltration can be a technically interesting way of obtaining technical lignin as it is or in combination with ways of fractionating lignin based on selective acid precipitation or extraction with organic solvents (Cui et al 2014;Lourencon et al 2015;Dodd et al 2015).…”
Section: Technical Significancementioning
confidence: 99%
“…Thus, ultrafiltration can be a technically interesting way of obtaining technical lignin as it is or in combination with ways of fractionating lignin based on selective acid precipitation or extraction with organic solvents (Cui et al 2014;Lourencon et al 2015;Dodd et al 2015).…”
Section: Technical Significancementioning
confidence: 99%
“…Selective precipitation and ultrafiltration are potentially useful techniques, depending on the intended lignin application (Brodin et al 2009;Toledano et al 2010;Ponomarenko et al 2014;Sevastyanova et al 2014;Duval et al 2015). It has been demonstrated that an increased content of OH aliph and OH phen groups improves the acetone solubility of lignin, which would be beneficial for fractionation based on acetone and hexane (Cui et al 2014). As hardwood lignins have a higher OH phen content, they would be more suitable for such fractionation.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard this application has the pivotal role in obtaining lignin with high purity (Cui et al 2014;Frigerio et al 2014). A deep chemical characterization was achieved by the GPC, FTIR, 2D-HSQC, and 31 P-NMR analyses.…”
Section: Lignin Characterizationmentioning
confidence: 99%
“…The major issue that precludes the complete utilization of lignin is that the SE process is not optimized to produce pure lignin (Cui et al 2014;Frigerio et al 2014), and the array of aromatic polymers obtained is contaminated by impurities such as ash and residual carbohydrates, which are often still covalently connected to lignin (Shevchenko et al 1999). While lignin extraction from black liquor, for example in the pulp industry, has already been extensively explored (e.g.…”
Section: Introductionmentioning
confidence: 99%